Diverse Roles of Neurotensin Agonists in the Central Nervous System - Boules, Mona; Li, Zhimin; Smith, Kristin; Fredrickson, Paul; Richelson, Elliott (Frontiers in Endocrinology, 2013)
NT is a tridecapeptide that is found in the central nervous system and the gastrointestinal tract. NT behaves as a neurotransmitter in the brain and as a hormone in the gut. Additionally, NT acts as a neuromodulator to several neurotransmitter systems including dopaminergic, sertonergic, GABAergic, glutamatergic and cholinergic systems. Due to its association with such a wide variety of neurotransmitters, NT has been implicated in the pathophysiology of several central nervous system (CNS) disorders such as schizophrenia, drug abuse, Parkinson’s disease, pain, central control of blood pressure, eating disorders, as well as, cancer and inflammation. The present review will focus on the role that NT and its analogs play in schizophrenia, endocrine function, pain, psychostimulant abuse, and Parkinson’s disease.